Early detection of psychosis: helpful or stigmatizing experience? A qualitative study. Issue 1 (11th September 2015) - Uttinger, Martina; Koranyi, Susan; Papmeyer, Martina; Fend, Fabienne; Ittig, Sarah; Studerus, Erich; Ramyead, Avinash; Simon, Andor; Riecher‐Rössler, Anita
Abstract: Aim: Despite the large scientific debate concerning potential stigmatizing effects of identifying an individual as being in an at‐risk mental state (ARMS) for psychosis, studies investigating this topic from the subjective perspective of patients are rare. This study assesses whether ARMS individuals experience stigmatization and to what extent being informed about the ARMS is experienced as helpful or harmful. Methods: Eleven ARMS individuals, currently participating in the follow‐up assessments of the prospective Basel F rüh e rkennung von P sy chosen ( FePsy ; English: E arly D etection of P sychosis) study, were interviewed in detail using a semistructured qualitative interview developed for this purpose. Data were analysed using Interpretative Phenomenological Analysis. Results: Most individuals experiencing first symptoms reported sensing that there was 'something wrong with them' and felt in need of help. They were relieved that a specific term was assigned to their symptoms. The support received from the early detection centre was generally experienced as helpful. Many patients reported stigmatization and discrimination that appeared to be the result of altered behaviour and social withdrawal due to the prepsychotic symptoms they experienced prior to contact with the early detection clinic. Conclusions: The results suggest that early detection services help individuals cope with symptoms and potential stigmatization rather than enhancing or causing the latter. More emphasis should be put on the subjective experiences of those concerned when debating the advantages and disadvantages of early detection with regard to stigma. There was no evidence for increased perceived stigma and discrimination as a result of receiving information about the ARMS.